Novel cryoballoon 180° ablation system for treatment of Barrett’s esophagus-related neoplasia: a first-in-human study - Overwater, Anouk; van Munster, Sanne N.; Nagengast, Wouter B.; Pouw, Roos E.; Bergman, Jacques J. G. H. M.; Schoon, Erik J.; Weusten, Bas L. A. M. (Endoscopy, 2021)
Background The novel 180° cryoballoon (CbAS180) enables semicircumferential treatment over a length of 3 cm per application. This first-in-human study evaluates its feasibility, efficacy, and safety for the treatment of Barrett’s esophagus (BE) neoplasia. Methods This multicenter study consisted of dose-finding and extension phases. Dose-finding started with the lowest dose possible (1.0 mm/s). For each dose, six patients were treated circumferentially over a 3-cm length. The dose was increased until the median BE regression was ≥ 60 % without serious adverse events (SAEs). In the extension phase, the dose was confirmed in 19 new patients. The outcomes were technical success, BE regression after one treatment, and SAEs. Results 25 patients (median Prague C0M3) were included (6 dose-finding/19 extension). In two patients, the CbAS180 could not be applied because of unstable balloon positioning. The technical success rate was 96 % (22 /23). In the six dose-finding patients, the starting dose resulted in median BE regression of 94 % (95 % confidence interval [CI] 60 %–97 %) without SAEs and was thus considered effective. Overall median BE regression was 80 % (95 %CI 60 %–90 %). Conclusion Single-session CbAS180 seems feasible, safe, and effective, and is a promising technique for the treatment of patients with BE neoplasia.